Estresse oxidativo e resposta inflamatória em cadelas submetidas à pneumoperitônio aquecido ou não em ovariohisterectomias - Milech, Vanessa (2018)
The present study aimed to evaluate the influence of carbon dioxide (CO2) on inflammatory and oxidative stress biomarkers on serum and peritoneal tissue, moreover, peritoneal histology in bitches submitted to video-assisted ovariohysterectomy. A sample of 20 female canines distributed in two groups was used, where patients in the heated group (HCD) (n=10) were submitted to pneumoperitoneum with CO2 heated at 37°C, and the unheated group (UCD) (n=10) subjected to cold CO2. The sample times for evaluation of inflammation and oxidative stress in blood and tissue corresponded to (T0) before cavity insufflation, (T1) after 30 minutes of pneumoperitoneum, and (T3) 60 minutes of CO2 exposure. We evaluated the serum biomarkers acetylcholinesterase (AChE), butyrylcholinesterase (BChE), myeloperoxidase (MPO), catalase (CAT), superoxide dismutase (SOD), thiobarbituric acid reactive substances (TBARS), reactive oxygen species (ROS), total thiols (t-SH) and reduced glutathione (GSH), as well as the biomarkers of oxidative stress CAT, SOD and TBARS in the peritoneal tissue. Additionally, histological analysis of the peritoneum was performed, evaluating congestion, hemorrhage, edema and the presence of inflammatory cells. AChE presented a difference between groups in T1 (p=0.0268) and T2 (p=0.0423), being higher in HCD, whereas BChE ranged between T0 and T2 of HCD (p=0.0175). The CAT activity was different in HCD between T0 and T1, and also T1 and T2 (p=0.0253), being higher in T1. There was a decrease in the levels of TBARS (p=0.0117) and GSH (p=0.0114), between T0 and T2 of UCD. The SOD, MPO, t-SH and EROS analyzes showed no difference. No differences were observed in the histological parameters evaluated. In CAT activity evaluation in tissue, the HCD presented a difference between T1 and T2 (p=0.0150), and comparing the groups, there was an increase in T2 of HCD (p=0.0288). In relation to SOD activity in the peritoneum, HCD was different on T2 in relation to T0 and T1 (p=0.0181), and in groups comparison, there was increase only in T1 of UCD (p=0, 0287). In the assessment of peritoneal TBARS, there was no difference between the moments or groups evaluated. Serum biomarkers, AChE and BChE, showed greater activity in HCD, indicating greater inflammation, and there was also a momentary increase in CAT, indicating oxidative stress in HCD. The use of warmed CO2 compared to unheated CO2 did not show changes in peritoneal histology, however, it was seen that the use of heated gas showed alterations in values of peritoneal oxidative stress markers (CAT and SOD) when compared to CO2 group not heated.